An investigation of the spatial and temporal distribution of kinetic energy in the mesosphere. The high latitude mesosphere - Nordaunet, Ole Kalstad (UiT Norges arktiske universitet, 2020)
The mesosphere is perhaps the least explored region in the atmosphere with very few methods of observing. This thesis will primarily be exploring a new technique for measuring the distribution of kinetic energy in the mesosphere across a wide range of spatial and temporal scales. The method being used relies on correlation functions between pairs of meteor measurements. These measurements are made using a network of specular meteor radars located in Northern Norway. This network produced 32 million meteor measurements over a 2 year period. The correlation function estimation method has been previously used on a smaller data set, but has so far not been used for a longer data set and at high latitudes. The main advantage of the new technique is that by studying the second order statistics of the wind field, we can obtain significantly better temporal and spatial resolution than before. Such a large data set allows for great resolution for both spatial and temporal correlation functions. By using temporal correlation functions and the kinetic energy spectrum, different atmospheric wave phenomena can be studied. These include diurnal and semi diurnal tides. The horizontal and vertical correlation functions will be used to verify that the kinetic energy follows a power law, as theoretically expected by the Kolmogorov theory for turbulence. This was done by using a second order structure function applied to correlation functions. The temporal and horizontal correlation functions were used to study the summer-winter variation in kinetic energy, some variation in the temporal domain is the impact from large scale waves as well as in the power spectra were there is a steeper power law slope during the winter. As for the horizontal domain there are differences in kinetic energy in the zonal and meridional direction for both large and small scale waves. The dataset in this thesis a lot more can be found out about the mesosphere, in this thesis only a few of the possibilities are explored. The results are in agreement with ...